2023
DOI: 10.3389/fmicb.2023.1157608
|View full text |Cite
|
Sign up to set email alerts
|

Genomic representation predicts an asymptotic host adaptation of bat coronaviruses using deep learning

Abstract: IntroductionCoronaviruses (CoVs) are naturally found in bats and can occasionally cause infection and transmission in humans and other mammals. Our study aimed to build a deep learning (DL) method to predict the adaptation of bat CoVs to other mammals.MethodsThe CoV genome was represented with a method of dinucleotide composition representation (DCR) for the two main viral genes, ORF1ab and Spike. DCR features were first analyzed for their distribution among adaptive hosts and then trained with a DL classifier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In particular, domestic pigs and probably other species in Suiformes played a key intermediate host role for all six historic influenza pandemics [ 6 , 16 , 17 , 18 , 19 , 20 ]. Suiformes are also one main family of mammalian hosts for CoVs [ 21 , 22 , 23 , 24 , 25 , 26 ]. Swine CoVs have been implied to replicate efficiently in human primary cells [ 27 ] and, more worryingly, cause infection in malnourished Haitian children [ 28 ] or calves and chickens [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, domestic pigs and probably other species in Suiformes played a key intermediate host role for all six historic influenza pandemics [ 6 , 16 , 17 , 18 , 19 , 20 ]. Suiformes are also one main family of mammalian hosts for CoVs [ 21 , 22 , 23 , 24 , 25 , 26 ]. Swine CoVs have been implied to replicate efficiently in human primary cells [ 27 ] and, more worryingly, cause infection in malnourished Haitian children [ 28 ] or calves and chickens [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis and other traditional methods in bioinformatics have provided indicative clues to infer the homology to other mammalian CoVs and the potential infection/transmission risk to these hosts of Suiformes CoVs. Phylogenetic trees have indicated that swine CoVs, such as swine acute diarrhea syndrome CoV (SADS-CoV) [ 21 ] and porcine epidemic diarrhea virus (PEDV) [ 25 ] may originate from bats [ 26 ]. Swine transmissible gastroenteritis virus (TGEV) has very high homology to canine CoVs [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation